2022
DOI: 10.3390/jcm11092676
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in Inflammatory Bowel Disease (IBD)

Abstract: Vaccines against SARS-CoV-2 are believed to play a key role in the suppression of the COVID-19 pandemic. However, patients suffering from inflammatory bowel diseases (IBD) were excluded from SARS-CoV-2 vaccines trials. Therefore, concerns regarding vaccination efficacy and safety among those patients were raised. Overall, vaccination is well tolerated in the IBD population, and different gastroenterological societies recommend vaccinating patients with IBD at the earliest opportunity to do so. Nevertheless, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Mass vaccination programs provide the best opportunity for controlling transmission and protecting populations [60], but this is a difficult decision for IBD patients as no confirmed data are presently available regarding COVID-19 vaccines in this population due to their exclusion from the conducted clinical trials [61]. The good news is that some recent studies have provided some clinical evidence [62][63][64]. Drug use after COVID-19 infection has also become a psychological burden for Crohn's disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mass vaccination programs provide the best opportunity for controlling transmission and protecting populations [60], but this is a difficult decision for IBD patients as no confirmed data are presently available regarding COVID-19 vaccines in this population due to their exclusion from the conducted clinical trials [61]. The good news is that some recent studies have provided some clinical evidence [62][63][64]. Drug use after COVID-19 infection has also become a psychological burden for Crohn's disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data on patients with inflammatory bowel disease (IBD) treated with high doses of systemic corticosteroids, infliximab, or infliximab and immunomodulators showed that they present a blunted response to the anti-SARS-CoV-2 vaccination [ 133 ]. However, a study on humoral and spike-specific T cell responses in patients with IBD who were on antimetabolite therapy (azathioprine or methotrexate), TNF inhibitors, and/or other biologic treatment (anti-integrin or anti-p40) for up to 6 months after completing two-dose COVID-19 mRNA vaccination showed that a spike-specific T cell response was not only induced in treated patients with IBD at levels similar to those of healthy individuals, but also was sustained at a higher magnitude for up to 6 months after vaccination, particularly in those treated with TNF inhibitor therapy [ 134 ].…”
Section: Immune Response To Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…To identify patients likely to develop severe COVID-19 and to facilitate medical decision-making, a multivariate model of predicting adverse outcomes was developed and validated [ 12 ]. The reality changed with the introduction of vaccines, which play a key role in the fight against the pandemic, but IBD patients have not been included in studies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%